北冰洋沉积物岩芯中厌氧细菌分布 - 高爱国; 陈皓文; 赵冬梅 (2009)
用逐步稀释法对北冰洋研究区10个沉积物岩芯(计189份样品)的厌氧细菌(AAb)进行分析,用改进的zObEll 2216号培养基,在4℃和25℃温度中分别培养3周以上,根据培养结果统计样品中厌氧细菌的检出率与含量,分析厌氧细菌含量的分布情况。结果表明,4℃时AAb检出率为85.71%,含量范围0--2.40x109个.g-1,平均4.42x107个.g-1;25℃时检出率为93.05%,含量范围0--1.10x109个.g-1,平均5.31x107个.g-1,略高于4℃时的平均值。研究表明研究区岩芯中广布AAb;温度的提高,可能提高AAb的相关指标;沉积物深度增加可能有利于AAb生长,但太深也不利于AAb生长,呈中层增高现象,但并不规则;在一定水深范围内,水深增加也有利于AAb的生长。同时给出了研究区内不同海域AAb分布差异。 189 samples divided from 10 sedimentary cores collected in the studied area of the Arctic Ocean are analyzed for anaerobic bacteria(abr.AAB) detection by means of the step-by-step dilution method.The samples respectively with the 4 ℃ temperature and the 25 ℃ have been cultured for 3 weeks to determine the AAB-detected rate and the content in the samples and to analyze the AAB distribution.As it is shown from the results,the AAB-detected rate of the 4 ℃ samples is 85.71% and the AAB contents range between 0 and 2.40×109 ind./g with an average of 4.42×107 ind./g,and the rate of the 25 ℃ is 93.05% and the contents range between 0 and 1.10 ind./g with their average of 5.31×107 ind./g,slightly higher than the 4 ℃ average.Therefore AAB is widely distributed in the cores from the studied area.It seems that the temperature increment is helpful for the increments of those indices.In addition,the sedimentary depths within the centain limit might be favourable to AAB growth.In general,the AAB contents become higher in the middle layers although it is not definitely regular.Water depth within a certain limit in the ocean might be also advantageous to AAB growth.The difference among the AAB regional distributions in the studied area is shown in the paper. 国家自然科学基金——楚科奇海及其邻近海域沉积物中细菌生物地球化学(40576060);楚科奇海沉积物中古环境变化的地球化学响应基金(40376017)